2021
DOI: 10.1183/16000617.0177-2021
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial pneumonia with autoimmune features: challenges and controversies

Abstract: The presence of clinical, serological and/or radiological features suggestive, but not confirmatory, of a defined connective tissue disease in patients with interstitial lung disease is a relatively frequent occurrence. In 2015, the European Respiratory Society and the American Thoracic Society proposed classification criteria for the interstitial pneumonia with autoimmune features (IPAF) research entity to capture such patients in a standardised manner, with the intention of nurturing clinical research. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
18
0
10

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 76 publications
4
18
0
10
Order By: Relevance
“…Our patient presented with respiratory failure that necessitated endotracheal intubation and mechanical ventilation at the initial diagnosis of IPAF, and she subsequently experienced recurrent episodes of acute exacerbation, which were all successfully ameliorated with methylprednisolone pulse therapy. A similar case with IPAF and respiratory failure was reported in a recent review [ 13 ]; the patient was successfully salvaged with methylprednisolone pulse therapy and six doses of cyclophosphamide. Based on the promising results of these two cases, glucocorticoid pulse therapy combined with cyclophosphamide may be an effective strategy for exacerbation of IPAF but warrants further studies.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Our patient presented with respiratory failure that necessitated endotracheal intubation and mechanical ventilation at the initial diagnosis of IPAF, and she subsequently experienced recurrent episodes of acute exacerbation, which were all successfully ameliorated with methylprednisolone pulse therapy. A similar case with IPAF and respiratory failure was reported in a recent review [ 13 ]; the patient was successfully salvaged with methylprednisolone pulse therapy and six doses of cyclophosphamide. Based on the promising results of these two cases, glucocorticoid pulse therapy combined with cyclophosphamide may be an effective strategy for exacerbation of IPAF but warrants further studies.…”
Section: Discussionsupporting
confidence: 66%
“…A recent review acknowledged that revision of IPAF criteria is required in the future given increasing published case and cohort reports. This review also provided a summary of the clinical, serological, and morphological domains, as well as treatments and outcomes among numerous IPAF cohorts [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compounding the poor assay characteristics, has been a marked increase in MSA requests, with our laboratory performing 1277 myositis LIA in 2021, increased from 548 in 2015. In our local population of 1.7 million, this equals 720 MSA requests per million, approximately 3 times the reported frequency in previous studies summarized by Lackner et al 3 High frequency of ILD diagnoses in our cohort may reflect reporting of ILD with autoimmune features (interstitial pneumonitis with autoimmune features, IPAF), which overlaps with CTD‐associated ILD 13,14 . This is a recently proposed subcategory of idiopathic fibrosing lung disease in which symptoms or serology may be suggestive of, but not sufficient to confirm, a CTD in the presence of ILD.…”
Section: Discussionsupporting
confidence: 53%
“…Despite similar radiographic patterns of fibrosis, IPAF patients have been reported to respond more favorably to immunosuppression. 13 In our cohort, 7 of 9 (78%) patients with ILD had an inconsistent ANA, of which 6 had negative or very weak (≤1:80) titers. Similar rates of ANA negativity were reported in a cohort of ILD screened by LIA, 15 where 27% (44 of 121 patients) were found to have an MSA, while studies using alternate methodologies for MSA detection, such as immunoprecipitation, found MSAs in 13% (35 of 269 patients).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation